Kinetics and mass transfer processes of thermal catalytic neutralization of gas emissions in modern waste processing complexes - Ved, V.; Tovazhnyansky, L. L. (Львівська політехніка, 2017)
The method for calculation, design and manufacturing of the catalytic converters for waste processing complexes has been developed. The development of the method and mathematical model of heterogeneous catalytic process of harmful impurities are based on the experimental study of parameters of the process catalytic thermal purification.